TUBERKULOMA SEREBRAL PADA PENDERITA ACQUIRED IMMUNE DEFICIENCY SYNDROME - Dony Ardianto,* Gama Sita Setya Pratiwi,* Vincent Ongko Wijaya,*,** Anton Mahendra,*,**Glennis Widra (NEURONA, 2020)
TUBERCULOMA IS A CENTRAL NERVOUS SYSTEM COMPLICATION WHICH RARE AND JEOPARDIZE DUE TO TUBERCULOSIS TB INFECTION THE AUTHORS REPORTS A CASE OF A 23 YEARS OLD FEMALE WITH HISTORY OF HUMAN IMMUNODEFICIENCY VIRUS INFECTION AND ACQUIRED IMMUNODEFICIENCY SYNDROME HIVAIDS AND UNDER TREATMENT FOR ACTIVE TB PRESENTED WITH HEADACHE AND DIZZINESS SINCE 1 WEEK BEFORE ADMISSION